2018
DOI: 10.1017/s0007114517003282
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of consumption of acerola, cashew or guava processing by-products on intestinal health and lipid metabolism in dyslipidaemic female Wistar rats

Abstract: This study assessed the effects of diet supplementation with industrial processing by-products of acerola (Malpighia emarginata D.C.), cashew (Anacardium occidentale L.) and guava (Psidium guajava L.) fruit on the intestinal health and lipid metabolism of female Wistar rats with diet-induced dyslipidaemia. Female rats were randomly divided into five groups: healthy control, dyslipidaemic control and dyslipidaemic experimental receiving acerola, cashew or guava processing by-products. Fruit processing by-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 72 publications
(88 reference statements)
3
59
2
5
Order By: Relevance
“…layer were evaluated in intestinal histological sections (15) . Inflammatory exudate, hyperaemia, haemorrhage, necrosis, preservation of the hepatic parenchyma (cell integrity, centralised nuclei and highly evident nucleoli) and degenerative processes (e.g.…”
Section: Histological Evaluation Of Liver and Intestinementioning
confidence: 99%
See 2 more Smart Citations
“…layer were evaluated in intestinal histological sections (15) . Inflammatory exudate, hyperaemia, haemorrhage, necrosis, preservation of the hepatic parenchyma (cell integrity, centralised nuclei and highly evident nucleoli) and degenerative processes (e.g.…”
Section: Histological Evaluation Of Liver and Intestinementioning
confidence: 99%
“…Inflammatory exudate, hyperaemia, haemorrhage, necrosis, preservation of the hepatic parenchyma (cell integrity, centralised nuclei and highly evident nucleoli) and degenerative processes (e.g. fat degeneration) were evaluated in liver histological sections (15) . Quantitative analyses of the intestinal morphometry of animals were also performed.…”
Section: Histological Evaluation Of Liver and Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…These fruit processing coproducts consist mainly of peels, seeds, and some mashed flesh, which are considered sources of compounds with different beneficial biological activities [5]. The consumption of acerola, cashew, and guava agroindustrial coproducts was reported to cause no damage to the histopathological characteristics of intestine and liver of rats, indicating the low potential toxicity of these materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…This constituent can be found in fruits, vegetables, and beverages. It has various ranges of biological functions such as antioxidant, blood lipid-lowering, anti-inflammatory and anti-carcinogenic [1][2][3][4][5]. NG has been determined using…”
Section: Introductionmentioning
confidence: 99%